1988
DOI: 10.1364/ao.27.003155
|View full text |Cite
|
Sign up to set email alerts
|

Crossover networks and their optical implementation

Abstract: Crossover networks are introduced as a new type of interconnection network for applications in optical computing, optical switching, and signal processing. Crossover networks belong to the class of multistage interconnection network. Two variations are presented, the half-crossover network and the full crossover network. An optical system which implements both networks is proposed and demonstrated. Crossover networks can be implemented using the full space-bandwidth product of the optical system with minimal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(20 citation statements)
references
References 10 publications
(8 reference statements)
0
20
0
Order By: Relevance
“…The method requires extension if it is to be applied to networks where the link permutations are not restricted to the class of bit-shuffling permutations, such as the crossover network [16], because of difficulties caused by a phenomenon the author calls tramline twisting. This will be the subject of a future paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method requires extension if it is to be applied to networks where the link permutations are not restricted to the class of bit-shuffling permutations, such as the crossover network [16], because of difficulties caused by a phenomenon the author calls tramline twisting. This will be the subject of a future paper.…”
Section: Discussionmentioning
confidence: 99%
“…The equivalence of these two networks was established by Wu and Feng in [7]. 5 In general, it may easily be shown that (16) A computer program implementing this formula can readily calculate the transformations for arbitrarily large switches.…”
Section: B Equivalence Of the Butterfly Network And The Omega Networkmentioning
confidence: 99%
“…Figure 2: Arrays of optical logic gates are interconnected with optical crossovers [6]. Fixed masks in the image planes block light at selected locations which customize the system for peiflc logic functions such as addition or sorting.…”
Section: Interconnect Mask Logicmentioning
confidence: 99%
“…Fixed masks in the image planes block light at selected locations which customize the system for peiflc logic functions such as addition or sorting. Figure 3 shows a schematic diagram of the optical crossover interconnect [6], which is one of a number of demonstrated methods of interconnection that is suitable for this model. An array of input beams is split into two identical copies.…”
Section: Interconnect Mask Logicmentioning
confidence: 99%
“…In this section we mention works that deal with the optical interconnections only, without consideration of the overall computing system architecture [30,31,32,33,34,35,36,37,38,39,40,41]. These studies concentrate primarily on optical systems to image arrays of sources onto arrays of detectors in an efficient manner.…”
Section: Architectures For Free-space Opticsmentioning
confidence: 99%